2009
DOI: 10.1007/s12272-009-1511-8
|View full text |Cite
|
Sign up to set email alerts
|

PAR-1622 is a selective peroxisome proliferator-activated receptor γ partial activator with preserved antidiabetic efficacy and broader safety profile for fluid retention

Abstract: Peroxisome proliferator-activated receptor (PPAR) gamma is known to be a key regulator of insulin resistance. PAR-1622 is a novel small molecule compound synthesized in Dong-A research center. In this study, we characterized the pharmacological profiles of PAR-1622, a selective partial activator of PPARgamma. In transient transactivation assays, PAR-1622 [(S)-2-ethoxy-3(4-(5-(4-(5-(methoxymethyl)isoxazol-3-yl)phenyl)-3-methylthiophen-2-yl)methoxy)phenyl)propanoic acid] showed a partial activator against human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, there is accumulating evidence that undesirable side effects, including body weight gain, anemia, fluid retention, and congestive heart failure, were seen in type 2 diabetic patients or animals treated with these compounds (13,16,27). Recent studies have developed a number of selective peroxisome proliferator-activated receptor modulators, including T2384, FK614, and PAR-1622, all of which are partial PPAR␥ agonists (23,30,31). The beneficiary effect of these insulinsensitizing compounds is that antihyperglycemic activity occurred independently of typical side effects in diabetic animals (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is accumulating evidence that undesirable side effects, including body weight gain, anemia, fluid retention, and congestive heart failure, were seen in type 2 diabetic patients or animals treated with these compounds (13,16,27). Recent studies have developed a number of selective peroxisome proliferator-activated receptor modulators, including T2384, FK614, and PAR-1622, all of which are partial PPAR␥ agonists (23,30,31). The beneficiary effect of these insulinsensitizing compounds is that antihyperglycemic activity occurred independently of typical side effects in diabetic animals (14).…”
Section: Discussionmentioning
confidence: 99%
“…The beneficiary effect of these insulinsensitizing compounds is that antihyperglycemic activity occurred independently of typical side effects in diabetic animals (14). Specifically, PAR-1622 or INT131 therapy does not increase plasma volume in ICR mice, whereas rosiglitazone therapy increases this (23,26). Collectively, these data raise Fig.…”
Section: Discussionmentioning
confidence: 99%
“…But, CIK cell movement via the blood circulation and CIK cell expansion at tumor sites depended on the number of CIK cells infused. Some reports showed that CIK cells first entered into the lung, after inoculation of nude mice (Hazelrigg et al, 2002; Kim et al, 2009), peaked there within 2–6 h after injection, then declined, and re-distributed to organs such as liver, spleen, and kidney within 24 h. Another report demonstrated that CIK cells infused via the tail vein homed directly to the RES (Li et al, 2011). In contrast, in our study aggregation and expansion of infused CIK cells mostly occurred in BM and spleen at the time of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…For PAR-5359 (67), which was claimed to be the first compound with balanced activities for PPAR and PPAR in vivo as well in vitro, the utilization as a pharmacological tool in elucidating the complex roles of PPAR / dual agonists was suggested [88]. PAR-1622 (68), on the contrary, is a selective modulator of PPAR (SPPAR M) with excellent antihyperglycemic activity and a broader safety margin against fluid retention compared to rosiglitazone [89]. These findings confirmed that partial activators of PPAR may be a promising approach for developing new drugs for the treatment of type 2 diabetes.…”
Section: -Alkoxy--phenylpropanoic Acid Derivativesmentioning
confidence: 99%
“…(19). The effects of chirality on the activity of these fivemembered "cyclized fibrates" were investigated by comparing the activity of the two pairs of enantiomers from the 2-ethyl-and 2-isopropyl-substituted derivatives (88) and (89). Interestingly, it was found that (S)-88 and (R)-89 were about 400 times more potent than their respective isomers.…”
Section: -Substituted Aryloxyacetic Acid Derivatives (Fibrates)mentioning
confidence: 99%